2005
DOI: 10.1103/physrevb.72.214511
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport inBi2+xSr2xCuO6+δ: Departure from the Wiedemann-Franz law i

Abstract: We present a study of heat transport in the cuprate superconductor Bi2+xSr2−xCuO 6+δ at subkelvin temperatures and in magnetic fields as high as 25T. In several samples with different doping levels close to optimal, the linear-temperature term of thermal conductivity was measured both at zero-field and in presence of a magnetic field strong enough to quench superconductivity. The zerofield data yields a superconducting gap of reasonable magnitude displaying a doping dependence similar to the one reported in ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 57 publications
(86 reference statements)
7
43
0
Order By: Relevance
“…In the only prior study on an underdoped cuprate (Bi-2201), the Lorenz ratio was found to be larger than expected: L/L 0 > 1.0. 50 However, values of L/L 0 exceeding 1.0 were observed only in samples whose normal state resistivity ρ a (T ) showed an upturn at low T , achieving residual values ρ 0 > 200 µΩ cm. 50 The violation was attributed to a metal-insulator transition.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In the only prior study on an underdoped cuprate (Bi-2201), the Lorenz ratio was found to be larger than expected: L/L 0 > 1.0. 50 However, values of L/L 0 exceeding 1.0 were observed only in samples whose normal state resistivity ρ a (T ) showed an upturn at low T , achieving residual values ρ 0 > 200 µΩ cm. 50 The violation was attributed to a metal-insulator transition.…”
mentioning
confidence: 95%
“…50 In all cases, the test was done on longitudinal conductivities (κ xx and σ xx ). Because of the large phonon term in κ xx , extracting the electronic term is done by extrapolating κ xx /T to T = 0.…”
mentioning
confidence: 99%
“…We cannot calculate the numerical value of L. Since numerical data of empirical quantities, through which it is expressed, are unknown. However, from the paper [24] of Proust et al we know that L is constant for fixed doping. Therefore, Eq.…”
Section: B Abdullaev D B Abdullaev C -H Park M M Musakhanovmentioning
confidence: 99%
“…The downturn has been widely accepted as a characteristic of non-Landau Fermi liquid behavior. As the next evidence for the non-Fermi liquid QPs property was recognized the fact that the cuprate Lorentz ratio was significantly larger than Sommerfeld's value [24].…”
Section: Resistivity Temperature Upturnmentioning
confidence: 99%
See 1 more Smart Citation